Evaluation of Daily Physical Activity (DPA) policy implementation in Ontario: surveys of elementary school administrators and teachers. (December 2016) - Allison, Kenneth; Vu-Nguyen, Karen; Ng, Bessie; Schoueri-Mychasiw, Nour; Dwyer, John; Manson, Heather; Hobin, Erin; Manske, Steve; Robertson, Jennifer
Abstract Background School-based structured opportunities for physical activity can provide health-related benefits to children and youth, and contribute to international guidelines recommending 60 min of moderate-to-vigorous physical activity (MVPA) per day. In 2005, the Ministry of Education in Ontario, Canada, released the Daily Physical Activity (DPA) policy requiring school boards to "ensure that all elementary students, including students with special needs, have a minimum of twenty minutes of sustained MVPA each school day during instructional time". This paper reports on the first provincial study evaluating implementation fidelity to the DPA policy in Ontario elementary schools and classrooms. Using an adapted conceptual framework, the study also examined associations between implementation of DPA and a number of predictors in each of these respective settings. Methods Separate cross-sectional online surveys were conducted in 2014 with Ontario elementary school administrators and classroom teachers, based on a representative random sample of schools and classrooms. An implementation fidelity score was developed based on six required components of the DPA policy. Other survey items measured potential predictors of implementation at the school and classroom levels. Descriptive analyses included frequency distributions of implementation fidelity and predictor variables. Bivariate analyses examining associations between implementation and predictors included binary logistic regression for school level data and generalized linear mixed models for classroom level data, in order to adjust for school-level clustering effects. Results Among administrators, 61.4 % reported implementation fidelity to the policy at the school level, while 50.0 % of teachers reported fidelity at the classroom level. Several factors were found to be significantly associated with implementation fidelity in both school and classroom settings including: awareness of policy requirements; scheduling; monitoring; use of resources and supports; perception that the policy is realistic and achievable; and specific barriers to implementation. Conclusions Findings from the surveys indicate incomplete policy implementation and a number of factors significantly associated with implementation fidelity. The results indicate a number of important implications for policy, practice and further research, including the need for additional research to monitor implementation and its predictors, and assess the impacts of study recommendations and subsequent outcomes of a reinvigorated DPA moving forward.